Emergency triage assessment for hypoxaemia in neonates and young children in a Kenyan hospital: an observational study. - Mwaniki, M; Nokes, D; Ignas, J; Munywoki, P; Ngama, M; Newton, C; Maitland, K; Berkley, J (2009)
OBJECTIVE: To describe the prevalence of hypoxaemia in children admitted to a hospital in Kenya for the purpose of identifying clinical signs of hypoxaemia for emergency triage assessment, and to test the hypothesis that such signs lead to correct identification of hypoxaemia in children, irrespective of their diagnosis. METHODS: From 2002 to 2005 we prospectively collected clinical data and pulse oximetry measurements for all paediatric admissions to Kilifi District Hospital, Kenya, irrespective of diagnosis, and assessed the prevalence of hypoxaemia in relation to the WHO clinical syndromes of 'pneumonia' on admission and the final diagnoses made at discharge. We used the data collected over the first three years to derive signs predictive of hypoxaemia, and data from the fourth year to validate those signs. FINDINGS: Hypoxemia was found in 977 of 15 289 (6.4%) of all admissions (5% to 19% depending on age group) and was strongly associated with inpatient mortality (age-adjusted risk ratio: 4.5; 95% confidence interval, CI: 3.8-5.3). Although most hypoxaemic children aged > 60 days met the WHO criteria for a syndrome of 'pneumonia' on admission, only 215 of the 693 (31%) such children had a final diagnosis of lower respiratory tract infection (LRTI). The most predictive signs for hypoxaemia included shock, a heart rate < 80 beats per minute, irregular breathing, a respiratory rate > 60 breaths per minute and impaired consciousness. However, 5-15% of the children who had hypoxaemia on admission were missed, and 18% of the children were incorrectly identified as hypoxaemic. CONCLUSION: The syndromes of pneumonia make it possible to identify most hypoxaemic children, including those without LRTI. Shock, bradycardia and irregular breathing are important predictive signs, and severe malaria with respiratory distress is a common cause of hypoxaemia. Overall, however, clinical signs are poor predictors of hypoxaemia, and using pulse oximetry in resource-poor health facilities to target oxygen therapy is likely to save costs.